Diary of a Wimpy Kid : Dog Days - Kinney, Jeff (UK Puffin Books, 2011)
The way I like to spend my summer holidays is in front of the TV, playing video games with the curtains closed and the light turned off. Unfortunately, Mom's idea of the perfect summer holiday is different from mine. Greg's mom has a vision of "family togetherness" that really doesn't sound a whole lot of fun.
Include Illustration
Keywords: Heffley, Greg (Fictitious character) -- Juvenile fiction